2015
DOI: 10.1007/s00439-015-1532-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of MARVELD2 and clinical phenotype in Pakistani and Slovak families segregating DFNB49 hearing loss

Abstract: Pathogenic mutations of MARVELD2, encoding tricellulin, a tricelluar tight junction protein, cause autosomal recessive non-syndromic hearing loss (DFNB49) in families of Pakistan and Czech Roma origin. In fact, they are a significant cause of prelingual hearing loss in the Czech Roma, second only to GJB2 variants. Previously, we reported that mice homozygous for p.Arg497* variant of Marveld2 had a broad phenotypic spectrum, where defects were observed in the inner ear, heart, mandibular salivary gland, thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In addition, the morphology of the Tric −/− mouse ES remained normal (Figure 3), with no indication of endolymphatic hydrops. These findings were compatible with the observation that Tric −/− mice show no disturbance in the sense of equilibrium, [10] and the fact that TRIC gene (DFNB49) mutations lead to hearing loss with no obvious vestibular phenotype in humans [9,16,17] .…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the morphology of the Tric −/− mouse ES remained normal (Figure 3), with no indication of endolymphatic hydrops. These findings were compatible with the observation that Tric −/− mice show no disturbance in the sense of equilibrium, [10] and the fact that TRIC gene (DFNB49) mutations lead to hearing loss with no obvious vestibular phenotype in humans [9,16,17] .…”
Section: Discussionsupporting
confidence: 79%
“…Linkage analysis of NSRHL segregating in family PKDF041 with STR markers across the genome, previously revealed linkage to DFNB49 locus on chromosome 5, with a maximum two-point lod score (Zmax) of 4.44 (θ = 0) for marker D5S2055 [ 13 ]. Subsequently, mutations in TRIC were identified as the cause of DFNB49 -linked HL [ 14 , 15 ]. Full sequencing of TRIC in the genomic DNA from two affected individuals from the PKDF041 family along with a normal hearing sibling did not reveal any pathogenic variants, suggesting there is an additional gene in the PKDF041 linkage interval in which a pathogenic variant is associated with deafness.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in MARVELD2 , which encodes tricellulin, and located at the DFNB49 locus, cause ARNSHL [ 31 ]. Seven different pathogenic variants of human MARVELD2 have been identified in patients with moderate to profound hearing loss [ 31 , 32 ]. Nayak et al reported that MARVELD2 mutations were responsible for about 1.5% of NSHL in their cohort of 800 Pakistani families[ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seven different pathogenic variants of human MARVELD2 have been identified in patients with moderate to profound hearing loss [ 31 , 32 ]. Nayak et al reported that MARVELD2 mutations were responsible for about 1.5% of NSHL in their cohort of 800 Pakistani families[ 32 ]. The splice junction mutation (c.1331+2T>C (IVS4ds+2T-C)) detected in our study has been recurrently reported in Pakistani population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%